1992
DOI: 10.1021/ja00033a042
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the preference for the chair conformation in the Cope rearrangement. Effect of phenyl substituents on the chair and boat transition states

Abstract: d,l-and meso-2,2'-bis[ 1 -methylene-1,2,3,4-tetrahydronaphthalenes] 8 and 9 were synthesized, and the activation energy parameters for their unimolecular [3,3] sigmatropic rearrangement to l,2-bis(3,4-dihydro-l-naphthalenyl)ethane (13) were determined. The d,l diastereomer is constrained to undergo Cope rearrangement in the chair conformation while the meso diastereomer is constrained to the boat. At 150 °C kdf fcmeM = 7 X 106. A comparison of activation energy parameters allows quantification of the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…However, an experimental study on the effect of phenyl substituents has shown that the energy difference between boat and chair transition states cannot be justified in terms of these interactions. 17 In fact, a simple force field model that takes into account only nonbonding steric interactions (MM2) is able to justify the differing stabilities of the two transition states. In summary, it can be concluded that if sufficient experimental or theoretical evidence were known at that time, serious doubts regarding the effectiveness of SOI would surely have been raised.…”
Section: Is the Hypothesis Of Soi Currently Justified?mentioning
confidence: 99%
“…However, an experimental study on the effect of phenyl substituents has shown that the energy difference between boat and chair transition states cannot be justified in terms of these interactions. 17 In fact, a simple force field model that takes into account only nonbonding steric interactions (MM2) is able to justify the differing stabilities of the two transition states. In summary, it can be concluded that if sufficient experimental or theoretical evidence were known at that time, serious doubts regarding the effectiveness of SOI would surely have been raised.…”
Section: Is the Hypothesis Of Soi Currently Justified?mentioning
confidence: 99%
“…To explain why the ketene group stabilizes 11 and 13 to nearly equal energies, we first note that Cope transition states can be viewed as a resonance hybrid of aromatic and diradical forms ) in model transition states 14 − 16 , we see that a diradical form contributes significantly to 16 -chair but not 16 -boat, a difference consistent with divergent radical-chair vs. aromatic-boat pathways in the ketene Cope reaction.…”
mentioning
confidence: 69%
“…As far as the mode of formation of 23 is concerned, the isomerization formally is a [3.3]sigmatropic rearrangement (Cope rearrangement). Since the rearrangement of structurally similar compounds [ 24 ], including the parent system hexa-1,5-diene, requires much higher temperatures than those given in Scheme 5 , we assume that the metalorganic reagent (or products derived therefrom) play a role in the isomerization.…”
Section: Resultsmentioning
confidence: 99%